2013
DOI: 10.1002/anie.201209959
|View full text |Cite
|
Sign up to set email alerts
|

A Small‐Molecule Zwitterionic Electrolyte without a π‐Delocalized Unit as a Charge‐Injection Layer for High‐Performance PLEDs

Abstract: Conjugated organic optoelectronic materials have attracted significant attention owing to their application in lightemitting diodes (LEDs), solar cells, thin-film transistors, optically amplified biosensor assays, and other areas. [1] For organic optoelectronic devices, interfacial modification between the organic material and the electrode is a crucial issue and becomes one of the most important research focal points, since charge injection/extraction affect device performance greatly. [2] Excellent charge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The synthetic routes have been described in a previous publication [45]. M1 and M2 are neutral amino derivates, while S1, S2 and S3 are zwitterionic ammonium derivates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic routes have been described in a previous publication [45]. M1 and M2 are neutral amino derivates, while S1, S2 and S3 are zwitterionic ammonium derivates.…”
Section: Resultsmentioning
confidence: 99%
“…Under the guidance of this theory, several specific functional groups are introduced to alcohol-soluble interface materials, such as ethylene oxide [35], phosphonate [36,37], amino [38][39][40][41][42] and ammonium [43,44]. In our previous study, we have reported a series of alcohol-soluble small molecules including amino and ammonium derivatives, and used them as charge-injection materials for polymer lightemitting diodes (PLEDs) [45]. We found that zwitterionic nature of the molecules is crucial important for the charge injection and p-delocalized structure is not absolutely necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the interfacial dipoles which are mainly generated from the modification of the metal electron density tail because of the presence of either ionic or polar groups could reduce the work function of cathode [28,29,20]. To investigate the effect of CPEs on the work function of the Al cathode, we measured the work function of Al and CPE-coated Al by using an ultraviolet photoelectron spectroscopy (UPS).…”
Section: The Work Function Of Cpe Covered Al Electrodementioning
confidence: 99%
“…Zwitterionic surfactants are electroneutral yet easily dispersed in high ionic strength solutions, and their reputation for biocompatibility is of great interest to the pharmaceutical and cosmetic industries; for example, phosphatidylcholines are often used in emollients to retain body moisture or treat skin diseases. 11 In materials science, zwitterionic surfactants can serve as novel charge injection materials for faster device response times in organic light-emitting diodes, 12 or as electrolytes that can combine high ionic mobility with water retention in solid-state supercapacitors. 13 …”
Section: Introductionmentioning
confidence: 99%